Supine Percutaneous Nephrolithotomy (PNCL)-2 Years’ Experience in a Tertiary Care Hospital: Experience of Supine Percutaneous Nephrolithotomy - Ali, Shoukat; Ali, Rashid; Jabbar, Maqbool; Karkar, Hayat Muhammad; Ullah, Ahmad (Pakistan Journal of Health Sciences, 2025)
Percutaneous Nephrolithotomy (PCNL) has basically substituted open surgery for managing large, complex renal stones. Supine PCNL provides multiple benefits compared to the prone position, yet its adoption in Pakistan remains limited. Objective: To evaluate the experience and outcomes of supine PCNL at a tertiary care hospital in Pakistan. Methods: This retrospective study included 113 patients (aged 3–74 years) who underwent PCNL at the Urology Unit of Baluchistan Institute of Nephro-Urology Quetta (BINUQ) between June 2021 and June 2023. Data on demographics, operative position (supine/prone), Extracorporeal Shock Wave Lithotripsy (ESWL) sessions, and postoperative hospital stay were retrieved from medical records. Descriptive statistics were analyzed using SPSS version 26. Results: Age of the patients was 32.68 ± 15.59 years. Among 113 patients, 63 (55.8%) were male, and 50 (44.2%) were female. Age distribution included 28 (24.8%) patients aged 3–20 years, 54 (47.8%) aged 21–40 years, 24 (21.2%) aged 41–60 years, and 7 (6.2%) aged 61–74 years. Right-sided PCNL was performed in 64 (56.6%) cases, while 49 (43.4%) involved the left kidney. A total of 82 (72.6%) patients experienced (Supine) PCNL, and 18 (15.9%) (Prone). The mean number of ESWL sessions was 0.24± 0.52, and the average postoperative hospital stay was 2.99 ± 1.85 days. Conclusions: Supine PCNL demonstrated favorable outcomes, including shorter hospital stays, effective stone removal, and reduced postoperative recovery time. This study supported the broader adoption of supine PCNL in clinical practice.